2021
DOI: 10.1063/5.0032610
|View full text |Cite
|
Sign up to set email alerts
|

Collisional ferrohydrodynamics of magnetic fluid droplets on superhydrophobic surfaces

Abstract: The study reports the aspects of post-impact hydrodynamics of ferrofluid droplets on superhydrophobic (SH) surfaces in the presence of a horizontal magnetic field. A wide gamut of dynamics was observed by varying the impact Weber number (We), the Hartmann number (Ha) and the magnetic field strength (manifested through the magnetic Bond number (Bo m )). For a fixed We~60, we observed that at moderately low Bo m ~300, droplet rebound off the SH surface is suppressed. The noted We is chosen to observe various imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…For example, fundamentals and applications for droplet impact between a specific surface and a specific impacting droplet have been rarely studied so far, despite its importance in applications such as liquid selection for targeted liquid transport, chemical reactions, or biological detections: the electriferous droplet would act differently when impacting on the non-wetting surface with different electric charges; the ferrofluid droplet would have special behavior when impacting on the surface under magnetic field; the chemical droplet would trigger a chemical reaction when impacting on chemical liquid film or solid surface. The particularity of specific combination of the impacting droplet and the solid surface or the liquid would be beneficial to practical applications, which is under tentative exploration [237][238][239] and remain elusive so far.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…For example, fundamentals and applications for droplet impact between a specific surface and a specific impacting droplet have been rarely studied so far, despite its importance in applications such as liquid selection for targeted liquid transport, chemical reactions, or biological detections: the electriferous droplet would act differently when impacting on the non-wetting surface with different electric charges; the ferrofluid droplet would have special behavior when impacting on the surface under magnetic field; the chemical droplet would trigger a chemical reaction when impacting on chemical liquid film or solid surface. The particularity of specific combination of the impacting droplet and the solid surface or the liquid would be beneficial to practical applications, which is under tentative exploration [237][238][239] and remain elusive so far.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Yun et al [8] distorted droplets using an electrospray device to attain non-axisymmetric shapes before impact on SH surfaces, and achieved droplet rebound suppression. During retraction of nonaxisymmetric (elliptic) shaped droplets, kinetic energy was noted to alternately switch between two perpendicular axes, resulting in insufficient kinetic energy in the vertical direction available for the rebound [8,23]. This finding contrasts with the spherical drops, where the uniform radial contraction results in rebound off the SH surface.…”
Section: Introductionmentioning
confidence: 97%
“…In case of non-Newtonian (Boger fluids) droplet impact dynamics, various factors like normal stress opposing the recoil dynamics, slowing down of receding contact line [6] and critical parameters like impact velocity and fluid elasticity [7] were identified to be the factors behind rebound suppression. Recently, Sahoo et al showed that by application of a transverse magnetic field at specific range of impact Weber numbers, droplet rebound can be inhibited [23]. Yun et al [8] distorted droplets using an electrospray device to attain non-axisymmetric shapes before impact on SH surfaces, and achieved droplet rebound suppression.…”
Section: Introductionmentioning
confidence: 99%
“…595 Related to ferrofluid droplet dynamics on superhydrophobic surfaces, the collision and post-impact dynamics of ferrofluid droplets show asymmetric spreading regimes and rebound suppression under the influence of a horizontal magnetic field. 596…”
Section: Ferrohydrodynamics Interfacial Instabilities Pattern Formati...mentioning
confidence: 99%